Development of data-driven framework for automatically identifying patient cohorts from linked electronic health records. (2017) - Fernández-Gutiérrez, Fabiola; Kennedy, Jonathan; Cooksey, Roxanne; Atkinson, Mark; Choy, Ernest; Brophy, Sinead; Zhou, Shang-Ming
No abstract available